Pembelajaran Berbasis Multimedia Interaktif Untuk Meningkatkan Literasi Sains Dan Teknologi - Sulis Winasti; Usep Soetisna; Anna Fitri Hindriana (Edubiologica: Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2018)
The literacy skills of science and technology in Indonesia is still low, and results from study science in Indonesia is still categorized as low. One of the efforts is the use of effective learning media that can ultimately improve the quality of learning outcomes. This study aims to determine the increase of science and technology literacy through interactive multimedia-based learning on the material of pollution impact for life. This study is Quasi Experiment with one group pretest-posttest design. The population in this study are all students of class VII of MTsN 7 Majalengka. The research sample is class VII E as many as 40 people. Analysis of the data used is normality test, homogeneity Wilcoxon test data from pretest and posttest. From this research found: 1) Characteristic of interactive multimedia based learning is video displays, video content, animations, contains questions, and narration to clarify video displays. 2) Characteristics of interactive multimedia is to have more than one media convergent (in the form of images, animation and video), interactive which is able to accommodate a user response, and be independent ie interactive multimedia provide convenience and completeness of the content so that it can use it without the guidance of others. 3) interactive multimedia-based learning can improve students' science literacy and technology in the material impact of pollution for life, by giving the conclusion increase is being considered. 4) Based on the results of questionnaires given to students after learning science by using interactive multimedia, student responses to the use of interactive multimedia, including in the medium category, meaning that most of the students in the experimental class had a good response to the interactive multimedia-based learning in science subjectsKeywords: Interactive Multimedia; Based Learning;  Literacy of Science; Technology